Research On Structure Design And Control Of Vehicle Platform Automatic Leveling System - Xing Zhuo Huang; Qi Yang; Wei Jia Yan; Yang Tian; Xun Yang Liang (淡江理工學刊, 2024)
In the vehicle leveling system, due to the overall volume is too large and other reasons, the leveling speed is slow, the leveling range is small, and the adjustment stability is insufficient. According to the characteristics of the three-legged parallel robot, this paper designs a new structure which is superior to the traditional hydraulic straight up straight down leg structure, and is superior to the traditional leveling system in both the leveling range and accuracy. The three-point leveling method is selected, and the basic center point leveling algorithm is improved. After the basic leveling operation is completed, the fine adjustment is added to further reduce the position error and improve the leveling precision. At the same time, according to the new structure, the connection between the dynamic and static platform is analyzed, and the linkage module between the leveling platform, the connecting rod and the corresponding slider is established. Then, through the simulation of platform tilt, the data verification is carried out directly with the algorithm results to improve the inspection efficiency.This paper proposes and designs a small vehicle-mounted leveling system with novel structure to solve the problems of the leveling range and the lack of stability of the existing small leveling platform, and completes its structural design, algorithm optimization and algorithm feasibility verification. It is intended to provide a new reference direction for small vehicle leveling system.